Sustainably improving Kenya's coffee production needs more participation of younger farmers with diversified income. (October 2018) - Wairegi, Lydia W.I.; Bennett, Mica; Nziguheba, Generose; Mawanda, Ashiraf; Rios, Carlos de los; Ampaire, Edidah; Jassogne, Laurence; Pali, Pamela; Mukasa, David; van Asten, Piet J.A.
Abstract: Kenya's Arabica coffee is highly rated in the world and is a major source of income for over half a million smallholder farmers. Production has declined by 50% over the past 25 years despite efforts by initiatives. This study tries to unravel what drives coffee production in Kenya. Data were collected on six cooperatives through household interviews and discussions with farmers, cooperative officials, and key informants. Yields ranged from ten to 3889 kg/ha/year, averaged 474 kg/ha/year and were positively correlated with intensity of crop management (r = 0.09, P < 0.05). Coffee represented about 25–50% of total household income. The oldest farmers (average 63 years) were poorer, had less diversified income sources and managed coffee less intensively than younger farmers. Intensity of management differed among cooperatives and was positively correlated with trust in the cooperative (r = 0.209, P < 0.001). Households that received credit from marketers were 30% more likely to use fertilizers than other households. We show that the yield gap can be closed by existing practices, and intensification is influenced by household characteristics and services received. We conclude that increasing the participation of young farmers in coffee production and creating an enabling environment for intensification can have a positive and sustainable effect on national production. Graphical abstract: Highlights: Annual coffee yields are poor but variability is high (yield and standard deviation ≈ 474 kg/ha). Maximum yields increase with intensity of crop management, and intensity of management was positively correlated to trust. Young farmers have more diversified income portfolios than old and poor farmers. Youngest farmers have smaller farms than oldest farmers, smaller coffee land, but better yields. Strengthening or targeting of younger and more entrepreneurial farmers is needed for sustainable and improved production.